Mobile Land and Building Tax Services as a Public Service Strategy: Between Accessibility and Taxpayer Compliance - Nathalie Suharto; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of mobile service units (mobling) at UPTB 2 Surabaya as a public service strategy to improve taxpayer compliance in paying Land and Building Tax (PBB), as well as to identify the gap between service accessibility and taxpayer compliance behavior. This research employed a descriptive qualitative approach, with data collected through participatory observation, unstructured interviews, and documentation. The findings show that the mobile service units have improved accessibility and simplified the tax payment process, particularly for taxpayers facing distance and time constraints. However, the improved accessibility has not been fully followed by consistent compliance behavior. Taxpayers still tend to make payments situationally, especially when dealing with administrative matters or when incentive policies, such as penalty waivers, are implemented. In addition, weak enforcement of sanctions and several administrative constraints continue to affect the level of taxpayer compliance. These findings indicate that the mobile service units are effective as a public service strategy in expanding access to tax payment services, but have not yet been fully effective in encouraging voluntary and sustainable taxpayer compliance.